The Influence of the Directors Boaards and Operational Profit and Loss on Tax Avoidance (Empirical Study of Sub-Oil and Natural Gas Companies Listed on the Indonesia Stock Exchange 2017-2022) - Abdilah, Abdilah; Raharjo, Naufal Adi; Riairawan, Pristanto; Taryanto, Taryanto (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The phenomenon of taxation in Indonesia is Indonesia's low tax ratio in 2021 which is recorded at only 9.11%, a low tax ratio indicates a high level of tax avoidance in a country. This study aims to determine the influence of the Board of Directors and Operational Profit and Loss on Tax Avoidance. Tax avoidance in this study is measured by the Cash Effective Tax Rate. This study used a sample of oil and gas companies listed on the Indonesia Stock Exchange during 2017 – 2022 using a purposive sampling method. The analytical method used is quantitative descriptive analysis. The results of this study indicate that the proxy for the board of directors, operational profit and loss has no effect on tax avoidance